Korelasi Sifat-Sifat Agronomi dengan Hasil dan Kandungan Antosianin Padi Beras Merah - Hafidh Prabowo; Djati Waluyo Djoar; Parjanto Parjanto (Agrosains : Jurnal Penelitian Agronomi, 2014)
Brown rice is a type of rice can be grown on land that is less water (upland). Brown rice has anthocyanin as an antioxidant. The purpose of this study was to identify brown rice agronomics characters that can be used as selection criteria to obtain brown rice which high anthocyanin. The experiment was conducted at the greenhouse of Agriculture Faculty, UNS using completed randomized block design consisting of 5 local varieties namely Mandel Wonogiri, Segreng Gunung Kidul, Segreng Boyolali, Segreng Wonogiri 1, and Segreng Wonogiri 2. Analysis of the data using the model Singh and Chaudhary (1979) are displayed in the form of a matrix correlation. Anthocyanin assays using the differential pH test method. The results showed that there was no difference between the anthocyanin content of varieties, but there is a tendency Segreng Boyolali varieties containing anthocyanins and Mandel Wonogiri higher. In general, varieties tested showed different potential yield, except Mandel Wonogiri varieties have low yield. The character of the total number of tillers, panicle length, and number of panicles per hill showed a strong correlation coefficient with the results. Plant height, number of panicles per hill, and the weight of 1000 seeds showed a high correlation coefficient with anthocyanin content.